Avaliação endoscópica das vias aéreas, perfil de gases sanguíneos, eletrólitos e do equilíbrio ácido-base em equinos submetidos ao treinamento de três tambores: João Pedro Borges Barbosa. - - Barbosa, João Pedro Borges [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Three barrel competition requires of high performance athletic horses. The race more used in this modality and the Quarter Horse usually begins training very young. To have success, the animals must have high speed and acceleration, requiring high performance athletic horses. Reviews endoscopic reveal a high prevalence of diseases of the System Respiratory as Exercise induced pulmonary hemorrhage in Athletes horses. For allow evaluation of post airways of horses, an endoscopy provides evaluate a blood amount deposited in the airways after exercises. Associated with endoscopic examination a blood gas analysis has been widely used in order to identify the behavior of gas exchange in high-performance horses, beyond for understanding of the balance electrolyte and acid-base in the animals find, possessing great value for understanding metabolic disorders. The present study goal was to assess how Airway, the profile of blood gases, electrolytes, acid-base balance of horses submitted the Three barrel training. Sixteen horses divided into two groups of 8 animals, regular training (RT - 5 times) and sporadic training (ET - 2 times a week) were used in the experiment. Endoscopy was performed before and 90 min after training. They were held two blood samples by puncturing the transverse facial artery before heating (M0) and immediately after training (M1), and the readings were performed with the I-Stat®. They were determined PCO2, PO2, SO2, pH, BE, HCO3 and TCO2, Na +, K +, iCa, Glucose, Hg e Ht. It was used ANOVA with repeated measures over time for comparisons of groups and time (p <0.05). The HFL befell was mild (1-2) the animals from both groups with 8/8 (100%) in the TR and 5/8 (62.5%) for the TE. Presence of serous trachea 4/8 (50%) for both groups. The EIPH befell was mild (1-2) the animals from both groups with 4/8 (50%) in the RT group and 3/8 (37.5%) for the TE group. Animals with grade 2 EIPH had mild hypoxemia and hypercapnia after exercise
Keywords: Equino; Endoscopia veterinaria; Exercicios; Eletrolitos; Equilibrio acido-base; Cavalo - Adestramento; Blood gas